Modern Approaches to Continuous Professional Education of Specialists at Medical University - P. S. Zhbannikov; V. I. Gorokhov (Moscow Polytechnic University, 2019)
The article addresses the issues of transition of additional professional education to a qualitatively new system - continuous medical education, which requires updating the structure of the organization of the educational process, as well as the content of additional professional programs. In 2016-2019 more than 300 completely new development programs have been worked out, reviewed and approved on the educational portal of the Ministry of Public Health of the Russian Federation. In 2016 Yaroslavl State Medical University has joined the project "Creation of model lean clinics" for promoting the principles of lean-management in healthcare. The main emphasis in the additional professional programs aimed at training medical specialists in the sphere of lean management is made on using simulation technologies. As a result, the University has developed an educational project based on simulation technologies "Process Factory PoLeanClinic" entailing the total immersion of participants in typical process with the aim to reveal, minimize, and forecast the losses and to raise the efficiency of medical organization. Since 2017 the University implements the concept of continuous professional education of teachers. This concept includes three basic elements: 1) continuing education in research and pedagogical activities; 2) continuing medical (pharmaceutical) education; 3) self-education. The elaborated learning modules for teachers' continuous education are based on the actual needs for acquisition or development of professional competences.